Pengaruh Debt to Asset Ratio dan Debt to Equity Ratio terhadap Return on Equity pada Perusahaan Properti dan Real Estate - Yunita Rizka Septiyani; Kristianingsih Kristianingsih; Muhamad Umar Mai (Indonesian Journal of Economics and Management, 2020)
The purpose of this research is to determine the Effect of Debt to Asset Ratio (DAR) and Debt to Equity Ratio (DER) to Return On Equity (ROE) of property and real estate companies listed in IDX for 2013-2017 both simultaneously and partially. The used research methods are descriptive and quantitative approaches, with secondary data using IBM SPSS Statistics 23 application tool. There are 40 sample data choosen by purposive sampling. Based on the results of the F test simultaneously Debt to Asset Ratio (DAR) and Debt to Equity Ratio (DER) have a significant effect on Return On Equity (ROE). Based on hypothetical testing, the t test bring the result that debt to asset ratio (DAR) has an insignificant effect on return on equity (ROE) variables and Debt to Equity Ratio (DER) has a significant effect on Return on Equity (ROE) variables on property and real estate companies listed in IDX.